Validation of Edinburgh post natal depression scale in post-natal woman from a tertiary referral center in South India - G., Rashmi A.; S., Shubhashri N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Pregnancy and childbirth are two most important life-changing events. Post-partum depression can affect mother and has a wide spectrum of presentation depending upon various social factors. Studies suggest that the incidence of postnatal depression among women of high social strata is 13-19% while the incidence is 11-42% among women with limited social support. The present study aims to study postnatal depression and its causes in a postnatal mother in all the aspects of social, physical, cultural and psychiatric grounds in the Indian scenario with the help of the Edinburgh postnatal depression scale (EPDS). Methods: From 1st July 2019 to 31st December 2019, a total 300 postnatal women between 1 to 6 weeks of the postpartum period participated and during their stay in the hospital responded to EPDS. The study was purposive sampling, and full consent of the study subjects was taken before the start of the study. Results: In this study, we found 20.1% of a woman affected by post-partum in South India. The higher percentage of severe depression was seen in the primary gravida (20%). The risk factors such as availability of postnatal care (with NICU admission), the woman with medical complications, late childbirth or delayed childbirth after marriage, multiparity, delivery via caesarean and nuclear family showed significant relationship (p<0.005) with depression. Conclusions: The present study, with a Post-natal depression of 20.1% along with the enumerated risk factors, suggest that the causes for postpartum depression (PPD) among working Indian woman, reflect a change to an urban-centric lifestyle. Further evaluation of these risk factors needs to be made and a routine screening of Postpartum depression (PPD) can help in improving maternal and child health.